2011
DOI: 10.3139/105.110124
|View full text |Cite
|
Sign up to set email alerts
|

Investigations on parameters influencing thermal and frictional properties within hot stamping

Abstract: In the automotive industry hot stamping of boron manganese steels represents one of the major technologies to manufacture crash relevant structures within body in white considering aspects of light weight construction. Hot stamping can be described as a non-isothermal hot sheet metal forming process. Temperature control in the forming process plays an important role. The process is quite complex as temperature dependent material and process properties such as flow curves, heat transfer and friction coefficient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

2014
2014
2017
2017

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 1 publication
0
5
1
Order By: Relevance
“…They explained the observed behavior with the diffusion phenomena of Fe and Al which are strongly influenced by the temperature. Several investigations like [15] and [16] measured increased adhesive wear due to increased contact pressure, which would contradict to the results of the current study. However, it has to be pointed out that the referenced studies observed the increased adhesive wear at the die radius.…”
Section: Discussioncontrasting
confidence: 99%
“…They explained the observed behavior with the diffusion phenomena of Fe and Al which are strongly influenced by the temperature. Several investigations like [15] and [16] measured increased adhesive wear due to increased contact pressure, which would contradict to the results of the current study. However, it has to be pointed out that the referenced studies observed the increased adhesive wear at the die radius.…”
Section: Discussioncontrasting
confidence: 99%
“…Due to the many process control variables that influence the result of forming as well as the mechanical properties of the component, the process layout tends to be portrayed as very complex, especially as the component geometry also plays an important role in it. In forming, the tribology for itself is determined to any substantial extent by a number of factors including austenitisation temperature [4] and duration [5], blank temperature during forming [5], workpiece coating [6], die surface (topology and material) [7], [8], die temperature [9] forming velocity [5], [10] and contact pressure [4], [6]. For the design of the dies, therefore, it is reverted to a thermo-mechanical Finite Elemente (FE) Simulation, with which it is possible, by means, for example, of sensitivity analyses, to quantify a number of parameter influences.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Ademaj et al (Ademaj, Weidig and Steinhoff 2013) observed a decreasing COF for increasing furnace time up to 360 seconds for all furnace temperatures (880-950 °C). Merklein et al (Merklein, Stoehr, et al 2011) observed a decrease in COF for longer furnace times (5 to 20 minutes 950 °C). They assume that the surface exhibits fragments of the oxide layer and they might change the friction mechanism from sliding to rolling.…”
Section: Furnace Time and Temperaturementioning
confidence: 95%
“…Three tool steels resulted in approximately the same COF and only HTCS 150 resulted in a higher COF. Merklein et al (Merklein, Stoehr, et al 2011) observed equal friction values if the standard deviation is taken into account for DIN 1.2367 and cast steel GP4M. Schwingenschlögl et al (Schwingenschlögl, Niederhofer and Merklein 2019) compared two hot work tool steels (DIN 1.2367 and DIN 1.2383) and measured similar friction coefficients.…”
Section: Tool Steel Gradesmentioning
confidence: 96%
See 1 more Smart Citation